Enzima redutase do nitrato em linhagens de arroz de terras altas submetidas ao estresse hídrico - Fernandes, Monique Carolina Nunes (2016)
Nitrogen is the main elemento required by the uplands rice crops. Its assimilation is a vital process that controls plant growth and development , ensuring good productivity levels. The rice crop’s capacity of reduce and incorporate nitrate has a fundamental importance to the success of this crop in highlands. Then, the aim of this work was study the activity of nitrate reductase enzyme in rice lineages during all development crop cicle, aiming at the select lineages more efficient in nitrogen use and correlate with the final productivity. The essay was made in field, in two different environments, with and without supplementary irrigation. The enzymatic activities was made in laboratory. It were evaluated 20 genotype of a VCU research from UFLA rice breeding program in partnership with EPAMIG and EMBRAPA. The experimental design was randomized block with three repetitions, and parcel constituted by 5 lines with 4 meters. Was obtained the nitrite quantity released by the vegetal tissues in incubation solution ( µmoles NO2- gmf -1 h-1) in seven sampling made in 7, 14, 21, 28, 45, 75 and 100 days after emergency (DAE), always in the morning, in all plots. The variance analysis was made in each sampling, and the averages were compared by the Scott-Knott test with 5% of probability and after that was made the correlation with the final productivity. The results showed that the treatments were divided in different groups statistically, showing that there are genetic variability among the tested materials and there are variability on the enzyme activity. The nitrate reductase enzyme behaved differently in the two environment, showing less activity in without supplemental irrigation, but, generally, its activity is higher in beggining of the crop and reducing with the time. The enzyme activity did not correlate significantly with the production, demonstrating an independent behavior of both characteristics. Concludes that the activity of the enzyme nitrate reductase, in rice is dependent on the genotype and the plant growth period, with higher expression in the beginning of the cycle. A reductase enzyme activity of nitrate should not be used alone for indirect selection in productivity character in rice upland, it is necessary to assess other features that complement the selection.